Multi-protocol exploratory treatment for metastatic castration-resistant prostate cancer with BRCA mutations: a case report and literature review - Zhao, Dongsheng; Su, Wen; Zeng, Liang; Hu, Guoqian; Tang, Jin (Frontiers in Oncology, 2023)
Most patients with metastatic hormone sensitive prostate cancer will progress to metastatic castration-resistant prostate cancer (mCRPC) ; Finding a highly effective, safe treatment with low recurrence rate has important clinical implications.Herein, we present a case of a 65-year-old man with castration-resistant prostate cancer treated by multi-protocol exploration. Magnetic resonance imaging (MRI) revealed prostate cancer invading the bladder, seminal vesicle glands, and peritoneum with pelvic lymph node metastasis. Transrectal B ultrasound puncture of prostate tissue was performed, and the pathological diagnosis was prostatic adenocarcinoma. CTC gene test was performed in peripheral blood, and the result showed BRCA1 gene mutation.The patient died of tumor complications after trying docetaxel combined with cisplatin chemotherapy, PARP inhibitor（ nilaparib）, PD-1 inhibitor （tislelizumab） and other treatments.This patient showed that the selection of an individualized combination chemotherapy regimen based on genetic testing results benefited the patient 's tumor control. When choosing a treatment regimen, problems such as failure to respond to re-chemotherapy and resistance to nilaparib may lead to deterioration of the condition.